Pengaruh Teknologi Gadget Terhadap Akhlak Siswa di SMK Swasta Yapim Indrapura Kabupaten Batu Bara - Amini, Nur; Nasution, Herry Syahbannuddin; Syahlan, Ali (STAI Tebing Tinggi Deli, 2024)
This study aims to analyze the influence of Gadget Technology on the Morals of Students at Yapim Indrapura Private Vocational School, Batu Bara Regency; to determine the level of use of Gadget Technology at Yapim Indrapura Private Vocational School, Batu Bara Regency and to determine the magnitude of the contribution of Gadget Technology to the Morals of Students at Yapim Indrapura Private Vocational School, Batu Bara Regency. This study is included in quantitative research. Quantitative research is research that uses numbers either directly taken from research results or data processed using statistical analysis. The results of the study indicate that the Category of the level of use of Gadget Technology at Yapim Indrapura Private Vocational School, Batu Bara Regency is included in the moderate category, which is in the interval 35.00 - 40.20 with an average value of 37.61. The t-count value is 14.056 with a sig. value of 0.001, thus it can be seen that the t-count value (14.056) is > than t-table (2.00958). Likewise with the sig value (0.001) <0.05. So it can be concluded that Ha is accepted, meaning that there is an influence of Gadget Technology on Student Morals at SMK Swasta Yapim Indrapura, Batu Bara Regency. The Determination Coefficient can be seen from the Adjusted R Square value of 0.497 or 49.7%. This shows that the variable Use of gadget technology (variable X) can affect student morals (variable Y) by 49.7%, the remaining 50.3% (100% -49.7%) is influenced by other variables that are not included in this study.